Antimicrobial susceptibility of Enterococcus species isolated from Slovak Bryndza cheese - Belicová, A; Krzková, L; Krajcovic, J; Jurkovic, D; Sojka, M; Ebringer, L; Duinský, R (Folia microbiologica, 2007)
Three hundred and ten enterococcal isolates (178 Enterococcus faecium, 68 E. durans, 49 E. faecalis, 8 E. italicus, 3 E. gallinarum, 3 E. casseliflavus, and 1 E. hirae) from Slovak Bryndza cheese were evaluated for susceptibility to nine antimicrobial agents (vancomycin, teicoplanin, ampicillin, streptomycin, gentamicin, erythromycin, rifampicin, nitrofurantoin, and ciprofloxacin). All enterococcal isolates from Bryndza cheese were susceptible to ampicillin, streptomycin, gentamicin, vancomycin, and teicoplanin as determined by the disk diffusion method. Vancomycin resistance genes vanA and vanB were not detected. Resistance rates of enterococcal isolates to rifampicin, erythromycin, ciprofloxacin, and nitrofurantoin were 24, 26, 2, and 1 %, respectively. Thirty-six % of E. faecium isolates and 22 % of the E. faecalis isolates were resistant to erythromycin. Resistance to rifampicin was similar in E. faecium (31 %) and E. faecalis (29 %). Both E. faecium and E. faecalis strains showed the same resistance to ciprofloxacin (2 %). E. durans isolates showed low levels of resistance to rifampicin, erythromycin, ciprofloxacin, and nitrofurantoin (1-4 %). Forty-eight (30 %) of the E. faecium isolates, two (3 %) of the E. durans isolates, and six (12 %) of the E. faecalis isolates exhibited multidrug resistance. The highest frequency of resistant enterococci was observed in Bryndza produced in winter season.
Keywords: Food Microbiology; léková rezistence; Slovakia; potravinářská mikrobiologie; Enterococcus; sýr; antiinfekční látky; Slovenská republika; Drug Resistance; Microbial Sensitivity Tests; mikrobiální testy citlivosti; Anti-Infective Agents; Seasons; roční období; Cheese